1993
DOI: 10.1083/jcb.123.6.1695
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular routing of GLcNAc-bearing molecules in thyrocytes: selective recycling through the Golgi apparatus.

Abstract: Previous experiments led us to speculate that thyrocytes contain a recycling system for GlcNAc-bearing immature thyroglobulin molecules which prevents these molecules from lysosomal degradation (Miquelis, R., C. Alquier, and M. Monsigny. 1987. J. Biol. Chem. 262:15291-15298). To confirm this hypothesis, the fate of GlcNAc-bearing proteins after internalization by thyrocytes was monitored and compared to that of fluid phase markers. Kinetic internalization studies were performed using 125I-GlcNAc-BSA and 131I-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Acidic pH, like denaturing agents, may induce a conformational change of Tg. Furthermore, the acidic pH effect may be physiologically relevant since Tg encounters acidic intracellular compartments during its secretion, uptake, and recycling by thyroid cells (23). As shown in Fig.…”
Section: I-tgf-␤ Binding Inhibitory Activities Of Untreated and Dss-amentioning
confidence: 94%
See 1 more Smart Citation
“…Acidic pH, like denaturing agents, may induce a conformational change of Tg. Furthermore, the acidic pH effect may be physiologically relevant since Tg encounters acidic intracellular compartments during its secretion, uptake, and recycling by thyroid cells (23). As shown in Fig.…”
Section: I-tgf-␤ Binding Inhibitory Activities Of Untreated and Dss-amentioning
confidence: 94%
“…Growth Inhibition of Rat Thyroid Cells by DSS-activated Tg-As described previously, Tg may encounter intracellular acidic compartments during internalization and recycling in thyroid cells (2,23). The thyroid cells are presumably the target cells for activated Tg.…”
Section: Tgf-␤ Antagonist and Agonist Activities Of Untreated And Dssmentioning
confidence: 99%
“…Chloroquine has been found to raise the pH of acidic compartments and to prevent the dissociation of lysosomal enzymes from their receptors. The resulting lack of free receptors can prevent the delivery of newly synthetized enzymes to their cellular destinations (Gonzalez Noriega et al 1980;Miquelis et al 1993). This can be the direct reason for the decrease in the enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid lectin recognizes Tg molecules exposing N -acetylglucosamin in the terminal position of the N -linked glycans of Tg (13). It is believed to recycle low-iodinated Tg molecules via the Golgi apparatus to the apical plasma membrane, where Tg becomes available for iodination by the thyroid peroxidase and is released into the lumen of thyroid follicles (14).…”
Section: Introductionmentioning
confidence: 99%
“…However, further experiments showed that the 46-kD Tg-binding protein differed from the cationdependent mannose-6-phosphate receptor (12). Another Tg-binding protein on thyroid epithelial cells is the so-called thyroid lectin (13), which is believed to mediate uptake of low-iodinated Tg molecules from the lumina of thyroid follicles (14). The thyroid lectin recognizes Tg molecules exposing N -acetylglucosamin in the terminal position of the N -linked glycans of Tg (13).…”
Section: Introductionmentioning
confidence: 99%